Care Coordination for Patients on Chronic Opioid Therapy Following Surgery: A Cohort Study. Issue 2 (August 2020) - Lagisetty, Pooja; Bohnert, Amy; Goesling, Jenna; Hu, Hsou Mei; Travis, Breanna; Lagisetty, Kiran; Brummett, Chad M.; Englesbe, Michael J.; Waljee, Jennifer
Abstract : Objective: To describe if patients with chronic opioid use with a consistent usual prescriber (UP) prior to surgery and if early return to that UP (<30 d) would be associated with fewer high risk prescribing events in the postoperative period. Summary Background Data: Over 10 million people each year are prescribed opioids for chronic pain. There is little evidence regarding coordination of opioid management and best practices for patients on long-term opioid therapy patients following surgery. Methods: The study design is a retrospective cohort study. We identified 5749 commercially insured patients aged 18 to 64 with chronic opioid use who underwent elective surgery between January 2008 and March 2015. The predictors were presence of a UP and early return (<30 d from surgery) to a UP. The primary outcome was new high-risk opioid prescribing in the 90-day postoperative period (multiple prescribers, overlapping opioid and/or benzodiazepine prescriptions, new long acting opioid prescriptions, or new dose escalations to > 100 mg OME). Results: In this cohort, 73.8% of patients were exposed to high risk prescribing postoperatively. Overall, 10% of patients did not have a UP preoperatively, and were more likely to have prescriptions from multiple prescribers (OR 2.23 95% CI 1.75–2.83) and new long acting opioid prescriptions (OR 1.69, 95% CI 1.05–2.71). Among patients with a UP, earlier return was associated with decreased odds of receiving prescriptions from multiple prescribers (OR 0.80, 95% CI 0.68–0.95). Conclusion: Patients without a UP prior to surgery are more likely to be exposed to high-risk opioid prescribing following surgery. Among patients who have a UP, early return visits may enhance care coordination with fewer prescribers. Abstract : Supplemental Digital Content is available in the text